Analisis Implementasi Nilai Karakter Gemar Membaca Pada Siswa Kelas IV SDN 5 Nanga Nuak - Rahmawati, Elvia; Nugraha, Asep Eka; Albar, Joni (STKIP Melawi, 2025)
Abstract: The research aims to analyze and describe the implementation of the character value of liking to read in class IV students at Nanga Nuak 5 Elementary School. The research method uses qualitative research with a descriptive analytical approach. The research was carried out at Nanga Nuak 5 Elementary School. The subjects in this research were fourth grade students, teachers and school principals. Data collection was carried out by observation, interviews and questionnaires using research instruments, observation sheets, interview sheets and questionnaires. The steps in presenting data include data processing techniques, data analysis, and data validity testing. The research results showed that the implementation of the character value of a love of reading was carried out by providing special reading time for students, providing reading facilities, creating and implementing programs that foster a love of reading, setting an example through teachers, and giving students the freedom to read as they wish. The implementation of the five indicators of the character of a love of reading can be concluded that the implementation of the character of a love of reading at class IV Nanga Nuak 5 Elementary School has been carried out well and effectively. This is proven by the efforts that have been made by teachers, principals, and student participation in its implementation both in the classroom and the school environment.Keywords: Implementation, Value, Character, and Fond of Reading.Â Abstrak: Penelitian bertujuan menganalisis dan mendeskripsikan implementasi nilai karakter gemar membaca pada siswa kelas IV SDN 5 Nanga Nuak. Metode penelitian menggunakan metode kualitatif dengan pendekatan deskriptif analitik. Penelitian dilaksanakan di SDN 5 Nanga Nuak. Subjek pada penelitian ini siswa kela IV, guru, dan kepala sekolah. Pengumpulan data dilakukan dengan obervasi; wawancara; dan angket; menggunakan instrumen lembar observasi; lembar wawancara; dan lembar angket. Langkah-langkah dalam menyajikan data meliputi teknik pengolahan data, analisis data, serta uji keabsahan data. Hasil penelitian diperoleh bahwa implementasi nilai karakter gemar membaca dilakukan dengan menyediakan waktu khusus membaca untuk siswa, menyediakan fasilitas membaca, membuat dan menerapkan program yang dapat menumbuhkan kegemaran membaca, memberikan keteladanan melalui guru, serta memberikan kebebasan pada siswa membaca sesuai keinginannya. Terlaksananya kelima indikator gemar membaca tersebut dapat disimpulkan bahwa implementasi karakter gemar membaca di kelas IV SDN 5 Nanga Nuak telah dilaksanakan dengan baik dan efektif. Hal ini dibuktikan dengan Upaya-upaya yang telah dilakukan oleh guru, kepala sekolah, dan partisipasi aktif siswa dalam pelaksanaaan implementasinyan baik di kelas maupun lingkungan sekolah.Kata Kunci: Implementasi, Nilai, Karakter dan Gemar Membaca.